Aktivitas Antibakteri Bahan Cetak Berbasis Ekstrak Natrium Alginat dari Alga Merah (Kappaphycus alverezii) terhadap Lactobacillus acidophilus - Putu Sadaka Putri Rahayu; Depi Praharani; Niken Probosari; Didin Erma Indahyani; Izzata Barid (Fakultas Kedokteran Gigi Universitas Jember, 2023)
Alginate impression material is a material that is often used for impression tissue in the oral cavity, and can be one of the agents of infection transmission in dental practice. Microorganisms can adhere to the mold such as Lactobacillus acidophilus bacteria. L. acidophilus were isolated from active caries and were considered as secondary invaders in the dental caries invasion process. The development of impression materials that have antibacterial capabilities needs to be done, one of which is by using materials derived from red algae (Kappaphycus alverezii). This plant contains a lot of alginate which is the main components of the cell wall, consisting of calcium, magnesium, sodium and potassium alginate salts. Synthesizing sodium alginate from red algae and analyzing the antibacterial activity of sodium alginate-based impression materials from red algae against L. acidophilus. Extraction of alginate from red algae using the acid method and conversion of alginic acid to sodium alginate by adding NaOH. The impression material is made with the addition of sodium alginate. Antibacterial activity test by well diffusion method. This study consisted of 3 groups, namely control (K), red algae sodium alginate extract (P1), and impression material with red algae sodium alginate extract (P2). Groups K, P1 and P2 had an average inhibition zone of 0 mm, 15.56 mm, 17.22 mm, respectively. Kruskal Wallis and Mann Whitney test showed significant differences between groups. Impression material based on sodium alginate extract from red algae has strong antibacterial activity against L. acidophilus.